Three-Dimensional Distribution of Platinum Group Minerals in Natural MSS-ISS Ores From the Norilsk One Deposit, Russia - Sittner, J.; Brovchenko, V.; Siddique, A.; Buyse, F.; Boone, M.; Renno, A.D.; Cnudde, V.; Merkulova, M.; Sluzhenikin, S.F. (Frontiers in Earth Science, 2022)
The Mt. Rudnaya MSS-ISS (monosulfide and intermediate solid solution) fine-grained ores from a NE termination of Norilsk 1 deposit were analyzed using a combination of X-ray computed micro tomography, spectral X-ray computed micro tomography and scanning electron microscopy to achieve both, 2D and 3D data. The ores consist of ISS composed of tiny lamellar intergrowths of cubanite and chalcopyrite solid solutions, which form up to 4-mm distinct globules surrounded by an ISS-MSS matrix. Our X-ray computed micro tomography results may provide 3D textural evidence of a possible natural sulfide-sulfide liquid immiscibility between Cu-rich and Cu-poor sulfide liquids that occurred before MSS and ISS were crystallized. The platinum group minerals (PGM) distribution shows that 20.6 vol% of all PGM occur in the ISS-MSS matrix and 79.4 vol% in the ISS globules. We suggest that this distributional behavior is due to the fact that the platinum group elements (PGE) cannot be dissolved in ISS, which led to the formation of the large PGM grains, which are up to 120 μm on their longest axis. The initial enrichment of ISS in PGE was controlled by differences in the partition coefficients of platinum and palladium between Cu-poor and Cu-rich liquids.